2006
DOI: 10.1099/ijs.0.63983-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromohalobacter nigrandesensis sp. nov., a moderately halophilic, Gram-negative bacterium isolated from Lake Tebenquiche on the Atacama Saltern, Chile

Abstract: A total of 52 strains of moderately halophilic bacteria isolated from hypersaline sediment of Lake Tebenquiche on the Atacama Saltern, Chile, were subjected to a taxonomic study. The morphological, physiological, biochemical and nutritional characteristics of the strains matched those described for the genus Chromohalobacter. Cells were Gram-negative, non-spore-forming, rod-shaped and motile. A black pigmentation was produced. One strain, designated LTS-4NT, grew optimally at 32 °C. Growth occurred in media co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…All of these species are moderately halophilic, aerobic, motile, Gram-negative, heterotrophic rods. Prado et al (2006) have isolated Chromohalobacter nigrandesensis and compared its properties with the above known species and found that it was closely related to Chromohalobacter species. A few extracellular halotolerant enzymes from Chromohalobacter species with great potential for use in industrial process have been characterized (Ventosa et al 1995(Ventosa et al , 1988.…”
Section: Introductionmentioning
confidence: 99%
“…All of these species are moderately halophilic, aerobic, motile, Gram-negative, heterotrophic rods. Prado et al (2006) have isolated Chromohalobacter nigrandesensis and compared its properties with the above known species and found that it was closely related to Chromohalobacter species. A few extracellular halotolerant enzymes from Chromohalobacter species with great potential for use in industrial process have been characterized (Ventosa et al 1995(Ventosa et al , 1988.…”
Section: Introductionmentioning
confidence: 99%
“…Moderately halophilic bacteria grow optimally in media containing 3–15 % (w/v) salt, but they can also grow at as high concentrations as 25 % (Ventosa et al 1998). This is the case of the species of Idiomarina , Halomonas , Oceanobacillus , Virgibacillus, Marinococcus and Chromohalobacter (Gurtner et al 2000; Heyrman and Swings 2001; Heyrman et al 2002, 2003; Ivanova et al 2000; Lu et al 2001; Maturrano et al 2006; Peng et al 2009; Prado et al 2006; Ripka et al 2006; Romano et al 2006; Wang et al 2008; Yoon et al 2004) and some species of the genera Bacillus and Staphylococcus (El-Rahman et al 2002; Heyrman and Swings 2001; Jeong et al 2013) that showed to be the closest relatives of the strains isolated in this study. Interestingly, the Nesterenkonia species were only isolated in media containing 20 % NaCl, in spite of the fact that they are considered to be moderately halophilic (Li et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moderately halophilic bacteria are widely distributed and are suspected to play an important role in the ecology of hypersaline habitats (Ventosa et al, 1998;Oren, 2002;Vargas & Nieto, 2004;Garcia et al, 2005b). There are currently as many as nine Chromohalobacter species reported in the literature (Garcia-Estepa et al, 2006;Peçonek et al, 2006;Prado et al, 2006;Aguilera et al, 2007), but none of these have been described as strains able to degrade aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%